(untitled) (Research, Society and Development, 2021)
Sleep is essential for the functioning of the organism and its vital functions, having a complex impact on the daily lives of individuals. Sleep deprivation and changes in its quality negatively affect several areas. Medical students are a class normally affected by such deprivation, given the high workload and strenuous lifestyle, showing consequences in academic, professional and personal life. This article shows the impacts of sleep deprivation in the face of course adversities, with consequences on students’ learning, performance and cognition. The integrative review was developed through the methods in stages of Identification of objectives; protocol planning; search strategies on MEDLINE, Lilacs, SciELO and Academic Google platforms; Works on sleep disorders in medical students, its impact on learning and/or obstacles directly related to deprivation, up to 10 years of publication, were included. Changes to achieve quality medical training, focused on mental health and quality of life for students, involve both the medical community, the cultural sphere and, above all, educational institutions.